2019
DOI: 10.7759/cureus.5574
|View full text |Cite
|
Sign up to set email alerts
|

Factors Leading To Meconium Aspiration Syndrome in Term- and Post-term Neonates

Abstract: BackgroundMeconium aspiration syndrome (MAS) is considered a major cause of respiratory morbidity. It is a common issue encountered in the delivery room and newborn nursery. There is a need to identify the factors that lead to MAS to develop strategies to screen such patients at an early stage to decrease the mortality and morbidity. The objective of this study was to determine the factors leading to MAS in neonates delivered at ≥37 weeks of gestational age.MethodsA cross-sectional study was conducted through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
2
12
0
2
Order By: Relevance
“…21 In present study, non-reassuring foetal heart rate was observed in 29 cases out of which 34% (n=8) neonates died and was statistically significant (p<0.05). Similar findings were reported by Chand et al 18 Fenton and Steer found a perinatal mortality of 21.4%, similar to present study, when foetal heart rate was 110 beats per minute or less in presence of meconium. 27 Resnick observed a perinatal mortality of 32% in presence of an abnormal foetal heart rate pattern when meconium was present which was consistent with our study.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…21 In present study, non-reassuring foetal heart rate was observed in 29 cases out of which 34% (n=8) neonates died and was statistically significant (p<0.05). Similar findings were reported by Chand et al 18 Fenton and Steer found a perinatal mortality of 21.4%, similar to present study, when foetal heart rate was 110 beats per minute or less in presence of meconium. 27 Resnick observed a perinatal mortality of 32% in presence of an abnormal foetal heart rate pattern when meconium was present which was consistent with our study.…”
Section: Resultssupporting
confidence: 93%
“…In similar study by Chand et al 48% were LSCS and 52% were vaginal deliveries. 18 Similarly, Urvashi et al, Sankhyan et al, Narang et al, Sori et al and Afsar et al noted an increase in number of LSCS ranging from 45% to 71.66% in MSAF. 16,[19][20][21][22] Increase in incidence of LSCS in our study was seen which may be due to good foetal monitoring during delivery and resorting to LSCS at earliest sign of foetal distress.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Accordingto a study conducted by Saroop, outof a total of 136 deliveries with meconiumamnioticfluid, 91 cases (67%) of them experienced intrauterine fetal distress (Chand et al, 2019). Andaccordingtoresearchconductedby Peter, there were 1061 deliveries with amniotic membranes, 51% ofwhom were accompanied by intrauterine fetal distress (Peter &Beverley, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Yoder, infants with meconium amniotic fluid with moderate to thick thickness were substantially increased in terms of precipitating factors, one of which was through the symptoms indicated by the presence of fetal distress (irregular fetal heart pattern, fetal acidosis) in contrast to infants without meconium and newborn with light meconium stain (P <0.01). In a study by Berkus et al, The medium and thick meconium groups had a fundamentally higher hazard, as evidenced by an abnormal fetal heart rate and cord blood vessels with a pH below 7.20 (markers of intrauterine fetal distress) (Chand et al, 2019). In a study by Tolu et al said that meconium-stained amniotic fluid is associated with increased frequency of operative delivery, birth asphyxia, neonatal sepsis, and neonatal intensive care unit admissions compared to clear amniotic fluid (Tolu et al, 2020).…”
Section: Risk Factorsforfetal Distress During Intrauterineinclude (1) Umbilical Cord Wrappingmentioning
confidence: 99%